Răspuns :
a+b+c=989 a+b=547 b+c=745. 547+c=989. c=989-547 c=442. b+442=745 b=745-442. b=303. a+303=547. a=547-303. a=244. a+b+c=989. 442+303+244=989.
a+b+c=989
a+b=547⇒b=547-a
b+c=745⇒c=745-b
c=745-(547-a)
c=745-547+a
c=198+a
inlocuim in prima ec si obt:
a+547-a+198+a=989
745+a=989
a=989-745
a=244
b=547-244
b=303
c=745-303
c=442
V: 244+303+442=989
sper ca te am ajutat
a+b=547⇒b=547-a
b+c=745⇒c=745-b
c=745-(547-a)
c=745-547+a
c=198+a
inlocuim in prima ec si obt:
a+547-a+198+a=989
745+a=989
a=989-745
a=244
b=547-244
b=303
c=745-303
c=442
V: 244+303+442=989
sper ca te am ajutat